EDUKASI PENTINGNYA MP-ASI SEBAGAI UPAYA PENCEGAHAN STUNTING DENGAN LEAFLEAT RESEP MP-ASI SEDERHANA DI DESA BOMAKI KEPULAUAN TANIMBAR SELATAN TAHUN 2026 - Arvicha Fauziah; Kasmiati Kasmiati; Kristiova Masnita Saragih; Jakob L.Jambormias (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Stunting is a pressing health issue in efforts to improve the quality of human resources, especially in Bomaki Saumlaki Village. The focus of community service aims to increase the knowledge of pregnant women and mothers of toddlers through the distribution of leaflets of simple MP-ASI recipes made from local ingredients. The quantitative method with a descriptive design. Community service activities include providing counseling. The leaflets contain information on stunting and MP-ASI recipes made with simple language and attractive illustrations. The results of community service showed a significant increase (p-value = 0.001) in community knowledge about stunting and the importance of MP-ASI. Collaboration between village midwives and the village government strengthens the sustainability of education. Awareness of participation and transformation of food consumption behavior at the household level.